Peningkatan Hasil Belajar Pengukuran Luas Menggunakan Pendekatan Pendidikan Matematika Realistik Indonesia di Kelas IV SDN 27 Anak Air - Syafen, Eksantia Kumala; Masniladevi, Masniladevi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2024)
This research aims to explain the increase in student learning outcomes in broad measurement material using the PMRI approach in Class IV SDN 27 Anak Air. The type of research was Action Research. The subject was 24 class IV students. Data analysis includes qualitative data analysis from observation sheets and quantitative data analysis from student learning outcomes. The research results showed that learning planning in cycle I obtained an average of 89.05% (B), increasing in cycle II to 96.8% (SB). Then the implementation in cycle I from the teacher aspect obtained an average of 89.25%, which then increased in cycle II to 96.4% (SB). Implementation in cycle I from the student aspect obtained an average of 87.46%(B), which then increased in cycle II to 96.4%(SB). The learning outcomes for cycle I obtained an average of 77.5(C), increasing in cycle II to 88.3%(B). It was concluded that using the PMRI approach could improve learning outcomes for measuring areas in class IV at SDN 27 Anak Air.